National Cyber-Security Policies oriented to BYOD: a proposal to Ecuador - Herrera, Andrea Estefania Vaca (2018)
There are some corporate policies in most of companies around the world, focus on mobile devices to be used as “Bring Your Own Device (BYOD)”, but in Ecuador, these policies are not being established yet. In spite of the fact, this technology has been used frequently, because of risk of security breaches, the employers don’t allow to use employees’ mobile devices, this solution is not convenient, because BYOD brings a lot of advantages like increased the Company’s economy and its communication and it can help to work at home, which now it is a good alternative. Business policies can be recommended from a national policy, as in many countries, but in the case of Ecuador, such policies are not present in a formal way, the regulatory framework of this human activity that must come from the state has not been developed, not only for regulate the activity, but also to guide its use in a safe and proper manner that provides privacy to users in all social economic activities, work, and other. This research is focused on the establishment of a policies baseline in Ecuador, then propose a National Policy on Cybersecurity focus on the use of mobile devices, which can be applied in the country as part of National Cybersecurity Policies.